MENINGKATKAN KEMAMPUAN MELAKUKAN GERAKAN SHOLAT MELALUI MEDIA VIDEO INTERAKTIF UNTUK ANAK TUNAGRAHITA SEDANG (Single Subject Research Kelas DIV C1 di SLB Bina Bangsa Padang) - Mimi Yusrita (Universitas Negeri Padang, 2015)
Abstract : This study was triggered by the problem found in SLB Bina Bangsa in wich one of its mentally retarded students in Class DIV C1 had difficulty in doing sholat movement. Thus, the objective of this study ws to show that onteractive video media can improve the bility of medium mentally retarded student in Class DIV C1 at SLB Bina Bangsa Padang in doing sholat movements. This was an experimental research which used Single Subject Design approach with A-B design and the data analysis technique was visual graphic analysis. The subject of this study was a medium mentally retarded student in Class DIV C1 at SLB Bina Bangsa Padang. The observation was carried out in two sessions. The first session was baseline (A) which was conducted in six times observation. It was found that the percentage of the student’s ability in doing sholat movements was between 18%% and 36%. The second session was intervention (B) by using interactive video media which was conducted in nine times observation. The result revealed that thepercentage of the student’s ability in doing sholat movements was between 36% and 84%. The data analysis in and between conditions had positive estimated tendency, stability, data tracking, and level changes. Moreover, the data overlap in the analysis between conditions were 0%which were very low. It means that the smaller the overlap percentage, the better the influence of intervention to target behavior change in this study. Hence, it was concluded that interactive video media can improve the ability of medium mentally retarded student in Class DIV C1 at SLB Bina Bangsa Padang in doing sholat movements. It was suggested to the headmaster to provide laptop to support teaching and learning process using video, so the learning will be more interesting. Kata Kunci : Media Video Interaktif; Gerakan Sholat; Anak Tunagrahita Sedang